Impact of Gender and Relationship Status on Young People’s Autonomy and Psychological Wellbeing - García-Castilla, Francisco Javier; Martínez-Sánchez, Isabel; Campos, Gema; Arroyo Resino, Delia (Frontiers in Psychology, 2020)
This study uses scales of autonomy and psychological wellbeing to determine whether young people’s gender and romantic relationship status give rise to differences in relation to a series of specific dimensions. To this end, we used Ryff’s Model of Psychological Wellbeing, which comprises several dimensions: self-acceptance, positive relations with others, autonomy, environmental mastery, personal growth, and purpose in life; and our own Transition to Adulthood Autonomy Scale (EDATVA), whose dimensions are: self-organization, understanding context, critical thinking, and socio-political engagement. As a result, a quantitative study was performed with 1,148 young people aged 16-21from Madrid, Spain and Bogotá, Colombia, of whom 60.2% were female and 39.8% were male. The findings show that in the gender variable there are differences between males and females in the dimensions of positive relations with others, personal growth (wellbeing questionnaire), and understanding context (autonomy questionnaire); the female sample obtained the highest scores. In the relationship variable, differences were found in environmental mastery and purpose in life; higher scores were obtained by young people in a romantic relationship. However, no differences were found in the different dimensions in the autonomy questionnaire between young people in a relationship and those not.